Changes in crop rotation productivity and stability of agrocenoses with prolonged use of fertilizers - E. I. Zolkina (Аграрная наука Евро-Северо-Востока, 2023)
The article considers the results of many years of field experiment (1968-2018) conducted in the Central part of the Non-Chernozem zone of Russia (Vladimir region). The research was carried out during eleven rotations of the four-field grain crop rotation. The study shows the effect of use of organic and mineral fertilizers applied in various doses and combinations on crop rotation yield, fertility of sod-podzolic sandy loam soil. It was found that the organomineral fertilizer system (manure 10 t/ha + N50P25K60) provided stable crop rotation productivity (on average for eleven rotations) at the level of 39.9 c. e./ha, or 79.7 % higher than the control without fertilizers. The mineral fertilizer system at medium doses of fertilizers (N50P25K60) was at the level of the organomineral system. The organic system was inferior in efficiency to the mineral system, both at medium doses (manure 10 t/ha) and at elevated doses (manure 20 t/ha). At the same time, the long-term use of organic fertilizers provided an increase in the humus content, depending on the dose of litter manure, by 16-36 % compared to the initial values. The use of organic fertilizers led to the stabilization of the content of available forms of potassium in the soil at an average and elevated level, respectively. Stabilization of the content of mobile phosphorus in the soil at the level of average supply was noted in mineral, organomineral and organic fertilizer systems, respectively, with low and medium doses. When using increased doses of fertilizers, there is a further increase in the content of nutrients in the soil. Growing crops in crop rotation without the use of organic and mineral fertilizers gradually led to a decrease in yield. The use of fertilizers provided greater stability of crop yields over the years of the study compared to the variant without fertilizers. The soil in the variants with organic (manure 20 t/ha) and organomineral (manure 10 t/ha + N50P25K60) fertilizer systems was characterized by high values of the main physiological groups of microorganisms. The ratio of the number of amylolytic and proteolytic microorganisms was 1.1-1.2, that indicated a balance in the processes of mineralization of organic matter in the soil and its humification.